2019
DOI: 10.1101/797449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conformational dynamics at microsecond timescale in the RNA-binding regions of dsRNA-binding domains

Abstract: Double-stranded RNA-binding domains (dsRBDs) are involved in a variety of biological functions via recognition and processing of dsRNAs. Though the primary substrate of the dsRBDs are dsRNAs with A-form helical geometry; they are known to interact with structurally diverse dsRNAs. Here, we have employed two model dsRBDs -TAR-RNA binding protein and Adenosine deaminase that acts on RNA -to understand the role of intrinsic protein dynamics in RNA binding. We have performed a detailed characterization of the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 63 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…A recent study from our lab has reported the presence of microsecond timescale dynamics in the two dsRBDs. Based on these results, we have proposed that the conformational ensemble of the dsRBDs might be responsible for the recognition of conformationally distinct target dsRNAs (38).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…A recent study from our lab has reported the presence of microsecond timescale dynamics in the two dsRBDs. Based on these results, we have proposed that the conformational ensemble of the dsRBDs might be responsible for the recognition of conformationally distinct target dsRNAs (38).…”
Section: Introductionmentioning
confidence: 90%
“…NMR relaxation data analysis for the D10RNA-bound TRBP2-dsRBD1 was carried out in a similar way as was done for apo-TRBP2-dsRBD1 described elsewhere (38).…”
Section: Nmr Relaxation Data Analysismentioning
confidence: 99%
See 3 more Smart Citations